Hepatitis Delta Virus Acts as an Immunogenic Adjuvant in Hepatitis B Virus-Infected Hepatocytes - Tham, Christine Y.L. (Cell Rep Med, 2020)
Hepatitis delta virus (HDV) requires hepatitis B virus (HBV) to complete its infection cycle and causes severe hepatitis, with limited therapeutic options. To determine the prospect of T cell therapy in HBV/HDV co-infection, we study the impact of HDV on viral antigen processing and presentation. Using in vitro models of HBV/HDV co-infection, we demonstrate that HDV boosts HBV epitope presentation, both in HBV/HDV co-infected and neighboring mono-HBV-infected cells through the upregulation of the antigen processing pathway mediated by IFN-β/λ. Liver biopsies of HBV/HDV patients confirm this upregulation. We then validate in vitro and in a HBV/HDV preclinical mouse model that HDV infection increases the anti-HBV efficacy of T cells with engineered T cell receptors. Thus, by unveiling the effect of HDV on HBV antigen presentation, we provide a framework to better understand HBV/HDV immune pathology, and advocate the utilization of engineered HBV-specific T cells as a potential treatment for HBV/HDV co-infection.